The Constitutional Court's Decision on the Perppu on Mass Organizations from the Perspective of Rechtsstaat and Critical Legal Studies - Bimantara, Arya; Salman, Radian (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
This study aims to analyze the Constitutional Court's consistency in reviewing the constitutionality of Government Regulation in Lieu of Law (Perppu) No. 2 of 2017 concerning Mass Organizations, which was later ratified as Law No. 16 of 2017. The study focuses on two main issues: first, whether the issuance of the Perppu meets the criteria of